Implementation Of Islamic Education With Blended Learning Model In New Normal Era - Aulia Nur Hayati; Lailatul Usriyah (Fenomena, 2023)
In the new normal era, educators seek to balance learners' safety and learning rights. However, because the quantity of learners in MIN 3 Banyuwangi is very much and they are required to comply with health protocols (primarily maintaining distance), the solution taken by MIN 3 Banyuwangi is implementing a blended learning model in teaching and learning activities (KBM). The focus of the problem in this study is the planning, implementation, and evaluation of Islamic education using the blended learning model. This study aims to determine the planning, implementation, and evaluation of learning using the combined learning model. Researchers use a descriptive qualitative approach to the type of case study. The data collection techniques use observation, interviews, and documentation. At the same time, the data analysis used is Miles, Huberman, and Saldana model data analysis consisting of data condensation, data display, and conclusion drawing/verification. Then, the validity of the data that researchers use is the source triangulation and triangulation techniques. This study obtained the following results: 1) MIN 3 Banyuwangi prepares learning scenarios and creates learning tools in planning activities. 2) in the implementation of learning, there are three activities: introduction, core, and closing. 3) as for learning evaluation, educators measure learners' learning outcomes from cognitive, affective, and psychomotor aspects through daily tasks, PTS, and PAS. In implementing PTS and PAS, MIN 3 Banyuwangi divided two groups. The upper class uses Computer-based Test mode, and the lower class uses paper and Pen mode. In addition, in the evaluation activities, the head of the madrasah has also reflected on the performance of educators by providing KBM journals and conducting socialization activities on "teacher performance assessment."